Vitamin D Status and Cognitive Performance of Post Stroke Patients - Rizaldy Pinzon; Vincent Ongko Wijaya; Dessy Paramitha (Cell and BioPharmaceutical Institute, 2021)
Background: The prevalence of post-stroke cognitive impairment (PSCI) ranges from 20-80%. Some studies found that vitamin D deficiency was common in stroke patients, yet the relationship with cognitive performance remains unclear. The study aimed to investigate the relationship between levels of vitamin D and cognitive performance in post-stroke patients.Materials and Methods: This was a cross-sectional study with 20 post-ischemic stroke patients. Vitamin D levels were measured using enzyme-linked fluorescent assay (ELFA). The cognitive performance was assessed by computerized mini-mental state examination (MMSE) and clock drawing test (CDT). The relationship between vitamin D levels and cognitive tests were performed using paired T-test.Results: Vitamin D insufficiency (<30 ng/mL) was experienced by all of the study subjects (100%), with the mean±SD of vitamin D level was 13.75±4.06 ng/mL. More than 70% subjects had cognitive impairment. Based on MMSE, patients with cognitive impairment had lower vitamin D levels, compared with those patients with normal cognition (13±4.38 vs. 16±2.44 ng/mL, p<0.001). In CDT examination, patients with cognitive impairment had slightly higher vitamin D levels, compared with those patients with normal cognition (13.93±4.25 vs. 13.33±3.93 ng/mL, p<0.001).Conclusion: The insufficiency of vitamin D on post-ischemic stroke patients appears to generate a bigger chance of PSCI occurrence. Physicians should be aware of vitamin D status of post-stroke patients, especially in the older population.Keywords: vitamin D levels, post-stroke cognitive impairment, risk factors